Fibroblast Growth Factors as Tools in the Management of Neuropathic Pain Disorders - Forouzanfar, Fatemeh; Sadeghnia, Hamid R. (Current Drug Targets, 2020)
Neuropathic pain is caused by a damage to or dysfunction of the somatosensory nervous system. The main mechanisms underlying neuropathic pain include ectopic activity in nociceptive nerves, peripheral and central sensitization, impaired inhibitory modulation, and microglial activation. Fibroblast growth factors (FGFs) make up a large family of growth factors that mediate neural development, metabolism, and function through three main key signaling pathways, including RAS/MAP kinase pathway, PI3 kinase/Akt pathway, and PLCγ. An association between the members of the FGF system and the improvement of neuropathic pain has become evident, recently. These signaling molecules may be expected to provide new drug targets for the treatment of neuropathic pain. To the best of our knowledge, it is the first study that reviews the relationship between some members of the FGF system and neuropathic pain.
Keywords: Fibroblast growth factors (FGFs)